KOMPOSISI NEMATOSIT KARANG FUNGIA, Cycloseris vaugani DARI TERUMBU KARANG PANTAI MALALAYANG, MANADO - Adelin M Sagrang; Carolus P Paruntu; Billy Theodorus Wagey; Kakaskasen A Roeroe; Medy Ompi; Adnan Wantasen (JURNAL PESISIR DAN LAUT TROPIS, 2021)
The purpose of this study was to determine the composition of nematocysts in the body tissue of the coral fungia, C. vaugani.  The location for the collection of C. vaugani colonies was on the coral reefs of the Malalayang coastal area, Manado. This research was carried out in September - December 2020. The observation of nematocysts of C. vaugani was carried out using an Olympus CX41 microscope with a magnification of x100 objective lens which connected to a computer monitor equipped with an optical view 7 application at the Fish Health Environment and Toxicology Laboratory, Faculty of Fisheries and Marine Science, UNSRAT.  The present results showed that C. vaugani had a composition of nematocysts, namely type I microbasic p-mastigophore (MpM-I) of 40.00%, small type II microbasic p-mastigophore (sMpM-II) of 31.11%, small holotrichous isorhizas (sHI) of 24.44 %, large type II microbasic p-mastigophore (lMpM-II) of 2.22%, and large holotrichous isorhizas (IHI) of 2.22%.  sMpM-II is the most dominant nematocyst type of C. vaugani and this type of nematocyst is thought to be used by coral for aggression and killing prey or predator if there is disturbance from the surrounding aquatic environment where the coral lives.  Further research is recommended to study the types and morphology of nematocyst from various species of coral fungia, including C. vaugani to understand the differences in their types and dimension of the nematocyst. Keywords: Composition, Cycloseris vaugani, Fungia, Manado, nematosit